The housing question in London : being an account of the housing work done by the Metropolitan board of works and the London county council between the years 1855 and 1900, with a summary of the Acts of Parliament under which they have worked - Londres (County), County council
plans depl. Titre de couv. : "The housing question in London 1855-1900"